KANDUNGAN MATERIAL ORGANIK DAN SIFAT GEOKIMIA BATULEMPUNG PALEOGEN DAN NEOGEN DI CEKUNGAN SERAYU: Suatu Analisis Potensi Batuan Induk Hidrokarbon - Edi Slameto; Hermes Panggabean; Syaiful Bachri (Pusat Survei Geologi, 2010)
Geochemistry analysis (Rock-Eval pyrolisis, GC and GC-MS) on 2 (two) samples of Paleogene claystone, 3 (three) samples Neogene claystone, and 1 (one) oil seepage sample in Serayu Basin. The result of analysis shows that TOC of the Neogene claystone is higher than the Paleogene claystone. One sample of the Neogene claystone is able to be classified as source rock for oil and gas, whilst the others including the Paleogene claystone show as gas source rock. The geochemistry composition of Neogene claystone at Gintung River indicates that the oil seepage can be correlated with the rocks. The kerogen type of all claystone in the area ranges from Type III (terrestrial) to Type II (mixing terrestrial and marine).Keywords: hydrocarbon source rock, Rock-Eval pyrolisis, gas chromatography, gas chromatography-mass spectrometry, Serayu Basin